A2 level psychology - Eysenck, Michael W.; Banyard, Philip, 1953- (Hove : Psychology Press, 2009)
This thoroughly updated new edition has been written specifically for the new AQA-A psychology A2-level specification for teaching from September 2009.
Includes bibliographical references and index.
Keywords: Psychology; Psychology -- Examinations -- Study guides; Psychology